2014
DOI: 10.1039/c3fo60590f
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of flavonoid-rich apples and nitrate-rich spinach on cognitive performance and mood in healthy men and women

Abstract: Flavonoids and nitrate in a fruit and vegetable diet may be protective against cardiovascular disease and cognitive decline through effects on nitric oxide (NO) status. The circulating NO pool is increased via distinct pathways by dietary flavonoids and nitrate. Our aim was to investigate the acute effects of apples, rich in flavonoids, and spinach, rich in nitrate, independently and in combination on NO status, cognitive function and mood in a randomised, controlled, cross-over trial with healthy men and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 74 publications
1
50
3
Order By: Relevance
“…Some (Gilchrist et al, 2014; Thompson et al, 2015, 2016; Wightman et al, 2015) but not all (Kelly et al, 2013; Bondonno et al, 2014; Thompson et al, 2014) studies conducted at sea-level have reported beneficial effects of NO3 supplementation on cognitive function. Prior to this investigation, to the authors' knowledge only one study had evaluated the effects of NO3 supplementation on cognitive function at simulated altitude (Lefferts et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some (Gilchrist et al, 2014; Thompson et al, 2015, 2016; Wightman et al, 2015) but not all (Kelly et al, 2013; Bondonno et al, 2014; Thompson et al, 2014) studies conducted at sea-level have reported beneficial effects of NO3 supplementation on cognitive function. Prior to this investigation, to the authors' knowledge only one study had evaluated the effects of NO3 supplementation on cognitive function at simulated altitude (Lefferts et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The large majority (12 of 13 studies) supplemented with nitrate or nitrate-rich foods; eleven trials used beetroot and one trial used spinach as sources of inorganic nitrate, and one study supplemented with sodium nitrite (see Table 1). As placebo, eight trials used nitrate-depleted beetroot juice (Kelly et al, 2013;Gilchrist et al, 2014;Lefferts et al, 2015;Rattray et al, 2015;Thompson et al, 2015;Thompson et al, 2016;Vanhatalo et al, 2016;Shannon et al, 2017), one studied employed nitrite-free capsules (Justice et al, 2015), two trials combined apple and blackcurrant juice (Thompson et al, 2014;Whitman et al, 2015) and one study did not report information on the control group (Bondonno et al, 2014).…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Participant health status and intervention duration: Two trials included patients with type 2 diabetes (T2DM) (Gilchrist et al, 2014;Shepherd et al, 2015), four trials included middle-aged and older healthy participants (Kelly et al, 2013;Bondonno et al, 2014;Justice et al, 2015;Vanhatalo et al, 2016) and the remaining seven trials recruited young healthy participants ( Table 1). The median BMI of the adults included in the trials was 24.6 kg/m 2 (range: 24.0 -30.8 kg/m 2 ).…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Research to date has investigated the cognitive enhancing effects of flavonoid-rich foods in participants with both normal cognitive function (16) and people with mild cognitive impairment (11-13) but effects in dementia patients remains under researched (17). In light of projections indicating rapid increases in the prevalence of the dementia (18) and in the absence of successful treatments, alternative measures to slow the development and progression of dementia are imperative.…”
Section: Introductionmentioning
confidence: 99%